(3EOGQI GdeNGWQ GdJTZjdjI aj GdCReGJ GdEbJUGOjI (B((3habG deYGjjQ (BBasell) /s - (3TjQjSJGd, LhSjas; (3HQjHjd, chQJ s ((3GdEScfOQjI(B: s (3GdecJH GdYQHj GdMOjK(B, s, 2009)
(3CSHGH hJYQja GdeNGWQ GdJTZjdjI, CSGdjH EOGQI GdNWQ GdJTZjdj, GdEHdGZ Yf GdNWQ hOhQ GdeYdheGJ hGdEJUGdGJ, GdELQGAGJ GdeMOOI dEOGQI GdNWQ GdJTZjdj, HGRd (B4 (3eJWdHGJ heYGjjQ QCS GdeGd WHbG ddCSGdjH GdeNJdaI, CSGdjH bjGS eJbOeI, eJWdHGJ QCS GdeGd dJZWjI GdNWQ GdJTZjdj aj GdTQcGJ GdESJKeGQjIs
(3edMb U(B.225 (3; GdeQGLY U(B.227s
Keywords: (3CNWGQ GdegfIs; (3GdCReGJ GdEbJUGOjIs; (3GdMhGOK GdUfGYjIs; (3GdeNGWQs